Prevalence and Factors Associated with Eating Disorders in Peruvian Human Medicine Students in the Context of the COVID-19 Pandemic: a Multicentre Study. - Zila-Velasque, J.P. (2025)
Introduction Eating disorders (ED) are serious conditions that have diverse consequences, associated with high morbidity and mortality: Among the factors associated with their development are, being female, and stress, which increased during the pandemic, and was higher in medical students. Our objective was to identify the prevalence and factors associated with ED in medical students. Methods Cross-sectional study, conducted with an online questionnaire, between January 1 and 31, 2021, in 22 universities, using the Eating Disorder Scale (EAT-26) and the Family Communication Scale (FCS). Generalized logistic regressions were used to identify the association between variables. Results A total of 1224 participants were recruited, and the prevalence was 12.5%. Associated factors included a poor perception of health in 34.3%, having a family and/or social environment member with an eating disorder in 21.7%, and medium or low satisfaction with family communication in 57.3% and 34.9% respectively, in addition to the academic year, dieting, concern for body image and the perception of inadequate eating. Conclusions Our results show that, in the context of the COVID-19 pandemic, 1-2 out of 10 Human Medicine students had an ED. The associated factors that influenced development of the condition included a fair or poor perception of health, the academic year completed, and medium or low satisfaction with family communication.